2020
DOI: 10.1038/s41598-020-72291-1
|View full text |Cite
|
Sign up to set email alerts
|

SMRT- and Illumina-based RNA-seq analyses unveil the ginsinoside biosynthesis and transcriptomic complexity in Panax notoginseng

Abstract: Panax notoginseng is one of the most widely used traditional Chinese herbs with particularly valued roots. Triterpenoid saponins are mainly specialized secondary metabolites, which medically act as bioactive components. Knowledge of the ginsenoside biosynthesis in P. notoginseng, which is of great importance in the industrial biosynthesis and genetic breeding program, remains largely undetermined. Here we combined single molecular real time (SMRT) and Second-Generation Sequencing (SGS) technologies to generate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 80 publications
0
7
0
Order By: Relevance
“…Currently, these two sequencing technologies have been used to study different regulatory mechanisms in multiple species. For example, more transcriptional splice events have been found in rice by combining these two technologies [ 15 ], and they have both been used to reveal the complexity of ginsenoside biosynthesis and the transcriptome in Panax notoginseng [ 16 ]. Thus, for the first time, we constructed full-length reference transcriptomes of I. lactea var.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, these two sequencing technologies have been used to study different regulatory mechanisms in multiple species. For example, more transcriptional splice events have been found in rice by combining these two technologies [ 15 ], and they have both been used to reveal the complexity of ginsenoside biosynthesis and the transcriptome in Panax notoginseng [ 16 ]. Thus, for the first time, we constructed full-length reference transcriptomes of I. lactea var.…”
Section: Introductionmentioning
confidence: 99%
“…The AS type ratios vary in different plants. In Dichocarpum and Arabidopsis , the shares of A3 and A5 were more than that of SE [ 5 ] (Table S1 ), analogous to other dicots such as soybean [ 48 ], Panax notoginseng [ 8 ] and Camellia sinensis var. assamica purple cultivar [ 13 ], among others; the same is true for monocots rice [ 4 ] and moso bamboo [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…One of the deterministic consequences is the adaptive shift of specialized metabolite biosynthesis. For example, 20,015 AS events of 6,324 Panax notoginseng genes were identified in PacBio transcriptome sequencing [ 8 ] (Table S1 ), many of which were associated with the ginsenoside biosynthesis. In the full-length transcriptome of Artemisia annua [ 9 ], 39 isoforms of 15 genes of the artemisinin biosynthesis pathway and upstream MVA and MEP pathways were identified.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, according to genomic and transcriptomic analyses, sesquiterpenoid synthesis-related genes were found and expressed in specific tissues. Previous studies were conducted to increase Chen et al, 2017;Xu et al, 2017;Zhang D. et al, 2017;Xue et al, 2019;Fan G. et al, 2020;Zhang et al, 2020; the yield of artemisinin by overexpressing the upstream or downstream enzymes, such as FPS and HMGR, but the artemisinin content did not increase significantly. Therefore, this study overexpressed the upstream, midstream and downstream enzymes [HMGR (AA201470), FPS, and DBR2] simultaneously to examine the content of artemisinin, and the revealed that the transgenic plants produced more artemisinin.…”
Section: Application Of High Throughput Sequencing In Bioactive Compo...mentioning
confidence: 99%